Japan's central administration at the crossroads: increasing public demand for deregulation, decentralization and de-bureaucratization - Akira, Nakamura (1998)
The Liberal Democratic Party (LDP) single handedly governed Japan for over thirty eight years until June 1993. Under the semi-permanent conservative governance, central agencies have assumed a major role in making Japanese big businesses expand and become one of the leading players in the international economy. Nonetheless, many Japanese doubt the role and function of Japan's central administration. They believe that the central government has been excessively involved in economic affairs. For them, governmental meddling in private business is detrimental to the health of Japanese society. Reflecting these public outcries, the government finally enacted an important law, The Law for the Promotion of Decentalization, on May 15, 1995. While much still remains to be clear, this may become a significant threshold for Japan's administrative reform. It may perhaps help introduce a new paradigm to Japan's producer oriented social environment. - Reproduced
Keywords: Administrative reform - Japan; Administrative reform